ANALISIS KEKERASAN PADA MASA PACARAN (DATING VIOLENCE) - Tisyah, Dewi Wulan; Rochana, Erna (SOCIOLOGIE, 2013)
The objectives of the research are to find out and explain about the reasons why violence happen, the kinds of violence which are happened during relationship, the effects of violence, victimsâ perspectives and the solution of the problem. The research uses case-study method with qualitative research. The determination the informant uses purposive sampling in which the informants are chosen intentionally based on the criteria and uses another people as key person or mediator in order the researcher can know and communicate with the informant. The techniques of data collection are deep interview, observation, and documentation. The findings of the research show that violence which are happened during relationship are caused by unfair gender culture, patriarchy culture, and relation of authority which is not equal and has developed and become entrenched of a society.Keywords: Dating violence